Hubungan Tingkat Stres Dan Status Gizi Terhadap Disminore Pada Remaja Putri - Rombe, Adriani Julyanti; Murti, Ni Nyoman; Noviasari, Damai (Akademi Kebidanan Bunga Husada Samarinda, 2024)
Dysmenorrhea is menstrual cramps or menstrual pain. Menstrual pain occurs mainly in the lower abdomen, but can spread to the lower back, waist, pelvis, upper thighs, and calves. Other problems that can cause dysmenorrhea are psychological factors and nutritional status. This study aims to determine the relationship between stress levels and nutritional status of female adolescents at SMAN 8 Balikpapan. Method this research analytical observational research with a cross sectional approach. Bivariate analysis using Spearman rank test. Result this research Sstatistical test results for the relationship between stress levels and dysmenorrhea with a p value of 0.000 and a correlation coefficient of 0.580, the results of the relationship between nutritional status and dysmenorrhea with a p value of 0.002 and a correlation coefficient of 0.373. The cause of dimenorrhea is psychological factors or psychological disorders of adolescents, adolescents who have unstable emotions will more easily experience menstrual pain. Nutritional status can cause dysmenorrhea, adolescents with abnormal nutritional status have a 1.2 times greater risk of experiencing dysmenorrhea. There is a relationship between stress levels and nutritional status on dysmenorrhea in young women at SMAN 8 Balikpapan